Uncertainty-Based Measurement of Job Satisfaction Evaluation of University Teachers: An Improved Bipolar Neutrosophic Multi-Criteria Approach for Enhanced Decision-Making - Jing Liu (Neutrosophic Sets and Systems)
Assessment of Job satisfaction in higher education persists as a complicated process involving many uncertain and regularly incompatible aspects. Old-style methods for quantifying job satisfaction are no longer able to account for growing uncertainty, paradoxes, and bipolarity in human opinions, a mix of satisfaction and dissatisfaction feedback. To fill this gap, we propose on bipolar neutrosophic decision-making (BNDM) approach to quantify job satisfaction within the vague, and bipolar nature of academic life. Our approach proposes a weighted bipolar neutrosophic cross-entropy technique to quantify optimization-based weighting of criteria. Then, we drive a weighted decision matrix and propose a bi-polar edition of evaluation based on distance from the average solution method to rank alternatives in a logical and appropriate way. Besides, we introduce a case study on job satisfaction among university teachers in the Middle East based on a questionnaire survey conducted across different universities. Proof-of-concept results are derived from the application of our approach to collected data to provide an in-depth analysis of aspects that might affect job satisfaction under uncertain and contradictory perceptions.